Early Primary Open-Angle Glaucoma - Lifferth, Austin R. (Canadian Journal of Optometry, 2018)
Glaucoma is the leading cause of irreversible blindness worldwide and is projected to affect more than 79.6 million people by 2020, over 10% of whom will be bilaterally blind.1 This multifactorial progressive optic neuropathy causes characteristic retinal nerve fiber layer damage that will eventually lead to associated glaucomatous visual field defects if left untreated. Unfortunately, these visual field defects are difficult for the patient to detect until more advanced stages and, as a result, early glaucoma is usually asymptomatic.2 This paper presents a case that is consistent with population studies that suggest that as many as half of people with glaucoma are unaware that they have the disease.3